(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to teaching students to speak English with the use of innovative educational technologies. The article reveals the cultural aspect in teaching speaking, the topic orientation stage,the issues of motivation.The technique of teaching speaking using interactive technology, such methods and techniques as "Story Map", "Prediction Chart", "Circles on the water", "Mind-Mapping"is described.The definition of the listed methods and brief information about the history of their creation are given.The use of these methods and techniques are supported by specific examples